Capacitor bank switching classification using scale selection continuous wavelet transform - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
Capacitor bank switching classification using scale selection continuous wavelet transform is an approach to develop power quality diagnostic feature to analyze the origin and possible cause of transient disturbance in the industry facility. The scale selection wavelet transform selectively perform continuous wavelet transform from scale 1 to scale 70 at the dilation interval of one per scale whereby it covers the frequency range from approximately 5.2kHz to 150Hz. This creates a wavelet domain segment known as transient zone. For frequency domain analysis, the transient zone at its scale analysis is used to analyze the transient frequency, energy and spectral content. The wavelet scale which corresponds to the highest energy is used to estimate the transient frequency. For time domain analysis, the wavelet scale 4 time plot was used to locate the instant, where the transient disturbance begins. These selected wavelet scales are used to create a segmentation window to capture the first cycle of the transient to determine its magnitude and duration. The scale selection wavelet shows excellent performance in term of effectively estimating and extracting the transient parameters for analysis and classifying the possible cause of normal, back to back and restrike capacitor bank switching.